SISTEM INFORMASI AKUNTANSI PEMASUKAN DAN PENGELUARAN PADA PERUSAHAAN DAGANG - Marini (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This paper discusses the application of the Accounting Information System (SIA) to manage inputs and expenditures on trading companies. This scientific work uses qualitative methods that describe in detail the object of research. The main source of data used is primary data obtained directly from the owner through interviews and observations of Menztore Banjarmasin, a trading enterprise that specializes in the sale of various types of men's outfits. Therefore, this scientific paper aims to evaluate the application of accounting information systems in the management of inputs and outputs at Menztore Banjarmasin, identify the obstacles encountered, and make recommendations for improving the system. Expected with a better understanding of SIA's role and benefits, trading companies can improve their financial management and long-term success